Evaluation of Requirements and Efficiency Parameters in the Use, Absorption, and Translocation of Nutrients in the Production of Hymenaea courbaril L. Seedlings, a Fruit Tree of Neotropical Importance - Bessa, Layara Alexandre; Reis, Mateus Neri Oliveira; Vitorino, Luciana Cristina; Silva, Fabiano Guimarães (Journal of Agricultural Studies, 2021)
The lack of sufficient knowledge on nutritional requirements, as well as efficiency parameters, in the use, absorption, and translocation of nutrients by seedlings in developmental stages may lead to the excessive use of chemical fertilizers, which end up contaminating the environment. Therefore, this research adopted the hydroponic system to elucidate the nutritional requirements of Hymenaea courbaril L. seedlings, a fruit tree of neotropical importance, throughout its development (30, 60, 90, 120, 150, and 180 days after transplantation). Consequently, biometric data on growth and mineral nutrition were obtained and utilized to determine efficiency parameters in the use, absorption, and translocation of nutrients. Although H. courbaril leaves functioned as efficient drains throughout the development, S and Fe accumulated in the roots, owing to their not very mobile nature. The macro and micronutrients that were accumulated the most in the tissues were N and Mn, which even suggested a tendency for H. courbaril to tolerate Mn concentrations that are naturally toxic. The most efficient adoption was observed for the S and Cu nutrients, whereas the most efficiently absorbed nutrients were N (the macro and micronutrient with the greatest accumulation) and Fe (the second micronutrient with the greatest accumulation). However, the seedlings efficiently translocated Ca-N and Mn, i.e., the most accumulated nutrients. Positive effects on growth were correlated with increases in P, Ca, and Mg levels, thus signaling the importance of an optimal supply of these nutrients in obtaining healthy seedlings of this species. This work suggests that to obtain seedlings of H. courbaril in practice, the availability of N, Mn, P, Ca and Mg should be reviewed.